Scanning electron microscopy in analysis of urinary stones - Racek, Martin; Racek, Jaroslav; Hupáková, Ivana (Scandinavian journal of clinical and laboratory investigation, 2019)
Urolithiasis is a frequent and in many cases serious disease. Proper analysis of kidney stone composition is crucial for appropriate treatment and prevention of disease recurrence. In this work, scanning electron microscopy (SEM) coupled with energy-dispersive spectroscopy was applied for a study of 30 samples covering the most common types of human kidney stones. The results are analyzed and evaluated in terms of applicability of the method for both routine kidney stone analysis as well as collecting of specific data. The method provides complex information about studied samples including morphology of the stones and of the present crystals or their aggregates. It also brings information on elemental composition of the phases. After application of standardization, quantitative microanalysis with detection limits of 400 ppm (Mg, P, S, Cl, K, Ca), 500 ppm (Na) and 1200 ppm (F) was obtained. Compositional mapping with EDS shows the elemental distribution within a sample. This study demonstrated that information on morphology and chemistry acquired by these methods was highly reliable for identification of phases, even when present in small amounts. It provided information on kidney stone structure, relationships between phases, major and minor element content, and variations in chemical composition related to the growth of the stones. SEM represents a powerful tool in urinary stone analysis, since a single facility can produce a wide spectrum of information. It can be suggested as a basic method used for routine urinary stone identification, whilst bringing additional detailed information that cannot be obtained by other methods.
Keywords: Spectrometry, X-Ray Emission; fosforečnany vápenaté; renal calculi; energy-dispersive X-ray spectroscopy; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; šťavelan vápenatý; Urinary Calculi; electron probe microanalysis; Humans; Urolithiasis; Apatites; scanning electron microscopy; apatity; lidé; Calcium Oxalate; spektrometrie rentgenová emisní; Calcium Phosphates; močové kameny